Improving Reading Comprehension in Kids with Special Needs - Alnemr, Murfet (Eximia, 2022)
Students with special needs such as autism, cognitive impairment, and learning disabilities, struggle when it comes to reading new material and cannot successfully comprehend the message due to a multitude of reasons that are explored in the article. This study researches the effects that technology can have in helping them comprehend what they read through the use of text-to-speech, interactive material, and other methods to better help engage and make sure they retain information.